What immunology has to say about pesticide safety - Friedrich, Adrián David; Zwirner, Norberto Walter (Frontiers in Immunology, 2024)
The use of pesticides has enabled the development of contemporary industrial agriculture and significantly increased crop yields. However, they are also considered a source of environmental pollution and a potential hazard to human health. Despite national agencies and the scientific community analyzing pesticide safety, immunotoxicity assays are often not required, poorly designed, or underestimated. Epidemiological evidence indicates that pesticide exposure increases the risk of developing cancer. Therefore, pesticides may not only act as carcinogens per se but also as immunosuppressive agents that create a permissive context for tumor development. Given recent evidence demonstrating the critical role of the immune response in cancer progression, we will highlight the necessity of assessing the potential impacts of pesticides on the immune response, particularly on tumor immunosurveillance. In this Perspective article, we will focus on the need to critically review fundamental aspects of toxicological studies conducted on pesticides to provide a clearer understanding of the risks associated with exposure to these compounds to human health.